Simulation platform of a free-space optical network under multipath fading channel. Issue 1 (May 2021) - Mallick, B; Parida, P; Palai, G
Abstract: This paper deals with channel modelling in free space optics (FSO) network using MATLAB 2017a. A detailed mathematical methodology to design an optical network is proposed under various small scales fading effects such as Rayleigh, and Rician fading which degrades the execution of a wireless channels. In the proposed work, the system is implemented at different sample rates, Various Doppler shifts through a flat fading channel. To modulate the data, Quadrature phase-shift keying (QPSK) modulation is used. The simulated effect of the fading channel of Rayleigh and Rician is contrasted in this paper.